2017
DOI: 10.7717/peerj.3101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various factors on Doppler flow ultrasonic radial and coccygeal artery systolic blood pressure measurements in privately-owned, conscious dogs

Abstract: ObjectiveThe purpose of this study was to assess the effects of age, body condition score (BCS) and muscle condition score (MCS) on indirect radial and coccygeal Doppler systolic arterial blood pressure (SAP) measurements in dogs.MethodsSixty-two privately-owned dogs were enrolled between June and July 2016. The BCS and MCS were determined by two investigators. Blood pressure was measured per published guidelines and using headphones, and the order of measurement site was randomized. Dogs were positioned in ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
(74 reference statements)
2
10
0
1
Order By: Relevance
“…In cats, no effect of obesity on BP was observed by oscillometry, but cats that were underweight had slightly lower BP when measured with Doppler than those that were of ideal body weight or obese . Recent studies suggested no association among body condition score, body weight, and SBP measurements in dogs or cats, but muscle condition score and sarcopenia have been reported to affect radial but not coccygeal BP measurements in the cat …”
Section: Normal Values For Canine and Feline Bpmentioning
confidence: 97%
“…In cats, no effect of obesity on BP was observed by oscillometry, but cats that were underweight had slightly lower BP when measured with Doppler than those that were of ideal body weight or obese . Recent studies suggested no association among body condition score, body weight, and SBP measurements in dogs or cats, but muscle condition score and sarcopenia have been reported to affect radial but not coccygeal BP measurements in the cat …”
Section: Normal Values For Canine and Feline Bpmentioning
confidence: 97%
“…Manuscript to be reviewed inappropriately-sized cuffs was associated with over-and underestimating indirect blood pressure when too small or too large a cuff was used, respectively, in one study of oscillometric pressure measurements in dogs (Bodey et al 1994). However, a similar association was not identified in a more recent study of indirect Doppler flow collected measurements (Mooney et al 2017). In this study, cuff size as a percentage of limb circumference was not correlated with blood pressure results.…”
Section: Discussionmentioning
confidence: 51%
“…Finally, screening of apparently healthy dogs was not performed in this or prior reports for diseases associated with hypertension, such as chronic hyperadrenocorticism, diabetes mellitus, or kidney disease. In one study that found no association between age and blood pressure, approximately half of enrolled dogs had at least one known disease (Mooney et al 2017), but only 20% of them had a disease known to be associated with hypertension. Positive associations in some studies, thus, could reflect agerelated vascular stiffening and loss of compliance (Acierno & Labato 2004;Meurs et al 2000) or merely an increased prevalence of diseases associated with hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dogs that were intolerant of the procedure, aggressive, or received sedation or anesthesia within the previous 12 h were excluded from the study. All other dogs, regardless of disease status or medications received, were included to best approximate a clinical population and allow comparison with prior studies (Bosiack et al, 2010; Hsiang, Lien & Huang, 2008; Mooney et al, 2017; Wernick et al, 2012).…”
Section: Methodsmentioning
confidence: 99%